1991
DOI: 10.1080/09670879109371568
|View full text |Cite
|
Sign up to set email alerts
|

Ticks of camels, sheep and goats in northwestern Kenya rangelands

Abstract: A survey to determine the species of ticks infesting camels, sheep and goats in the semi-arid rangelands of Kenya showed that Hyalomma trancatum, Hyalomma dromedarii and Rhipicephalus pravus were the most abundant, in that order. Most of the ticks were restricted to the predilection sites with evidence of tissue damage. When this occurred on the lower extremities of the limbs, abscesses and lameness developed. In camels, ticks attached on the eyelids causing excessive irritation, lacrimation and conjunctivitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Results of the present study revealed that examination of 882 of the various domestic animals species, of which 551 were camels, 225 sheep and 106 goats in Shalatin city, Red Sea governorate, Egypt. Out of 551 camels 154 (27.94%) were found infested with H. dromedarii represented the main tick species infesting camels followed by H. impeltatum, H. a. anatolicum and Amblyomma lepidum, These results were in agreement with, the results obtained by Njanja et al (1991); Van Straten and Jongejan (1993); Diab et al (2001); Abdel-Baki (2001); Mazyad and Khalaf (2002); Iqbal (2005); Mamak et al (2006). It was also found that H. dromedarii females were the main tick species found engorged on the camels, while females of the other species; only partially engorged.…”
Section: Discussionsupporting
confidence: 81%
“…Results of the present study revealed that examination of 882 of the various domestic animals species, of which 551 were camels, 225 sheep and 106 goats in Shalatin city, Red Sea governorate, Egypt. Out of 551 camels 154 (27.94%) were found infested with H. dromedarii represented the main tick species infesting camels followed by H. impeltatum, H. a. anatolicum and Amblyomma lepidum, These results were in agreement with, the results obtained by Njanja et al (1991); Van Straten and Jongejan (1993); Diab et al (2001); Abdel-Baki (2001); Mazyad and Khalaf (2002); Iqbal (2005); Mamak et al (2006). It was also found that H. dromedarii females were the main tick species found engorged on the camels, while females of the other species; only partially engorged.…”
Section: Discussionsupporting
confidence: 81%
“…The high burden of this tick next to Rh. pulchellus on camels reared in the lowland arid agroecological zone of Kenya [ 66 ] supports the above explanation. Moreover, the tick appears to harbor an agent of Q fever; thus, an epidemiological study about this zoonotic infection should be initiated in the lowland arid and semi-arid agroecologies to design control strategies.…”
Section: Discussionmentioning
confidence: 61%
“…Moreover, evidence reveals that Hy. dromedarii infests camels and ruminants in arid and semi-arid agroecologies of East African countries such as Kenya, Sudan, and Somali [ 63 , 66 , 67 ]. Interestingly, the absence of this tick in the western region, including B-G of Ethiopia and South Sudan, a country that borders Ethiopia at a western location, is evidence of the unsuitability of the area for this tick.…”
Section: Discussionmentioning
confidence: 99%
“…Tick are known as vector of various pathogenic agent that cause serious disease for human and domestic animals .All tick undergo four basic stages in their life cycle-Eggs , larva ,nymph and adult.Furthermore, they have one host tick, like Boophilussp , two host tick and three host tick like Rhipicephalusspp (6). Whether(17)to the mentioned most abundant ticks found in the ears, eyelids, lips of sheep and goat likeHyalommaanatolicumanatolicum, Hyalommamarginatumisaaci, Rhipicephalushaemophysaloidesand Haemophysalisbispinosa.Tick bit might be causingdirectly mechanical tissue damage , irritation , hypersensitivity , abscess and when present in large number would cause anemia and reduce productivity (13); (20).…”
Section: Introductionmentioning
confidence: 99%